The Philosophical Construction of Educators in Islamic Education: An Ontological, Epistemological, and Axiological Analysis - Fatkhul Mubin; Abd Aziz (GAPAI: Jurnal Pendidikan Agama Islam, 2026)
This article examines the philosophical construction of educators in Islamic education through ontological, epistemological, and axiological perspectives. Ontologically, educators are understood not merely as professional instructors but as moral, intellectual, and spiritual agents responsible for guiding the holistic development of learners. Within the Islamic educational tradition, educational authority is associated with Allah as the ultimate source of knowledge, Prophet Muhammad as the exemplary educator, parents as the primary educators, and teachers as professional actors within educational institutions. Epistemologically, the authority and responsibilities of educators derive from the integration of revealed knowledge, rational inquiry, ethical reflection, and educational experience. This integrated foundation distinguishes Islamic educational philosophy from secular approaches that tend to separate professional teaching practices from divine and moral authority. Axiologically, educators are entrusted with transmitting knowledge, cultivating virtuous character, strengthening religious consciousness, and preparing learners to contribute responsibly to society. Therefore, the ideal educator in Islamic education must possess personal-religious, socio-religious, and professional-religious competencies. These competencies integrate pedagogical expertise, spiritual integrity, social responsibility, and ethical conduct. The article argues that educators occupy a central position in Islamic education because their professional responsibilities are inseparable from moral accountability and spiritual commitment. This philosophical framework offers a comprehensive foundation for reconstructing educator professionalism in response to contemporary educational challenges.